The Development of Russian Military Doctrine Post Cold War and Its Implications For Ukrain - Farid, Ishak; Suprayitno, Eri; Gurnadi, Dudi; Anggun, Yuliana; Widodo, Pujo (Devotion : Journal of Research and Community Service, 2022)
Russia's decision to carry out an attack on Ukraine by conducting a special military operation or invasion was carried out on the grounds of protecting its national interests. Military doctrine, which is defined as a guideline and strategy, becomes one of the bases for formulating a country's defense policy and foreign policy in establishing cooperation or conducting conflict. This study aims to understand Russia's post-cold war military defense doctrine, which became the basis for its actions to carry out military attacks on Ukraine. The method in this research is descriptive by referring to the literature and reliable documents. Collecting data using literature review of various documents, journals and news as well as data analysis using qualitative. The results of the study show that the military operations carried out by Russia in Ukraine are inseparable from changes in military doctrine carried out after the cold war which made the nature of defense more offensive. This military doctrine later became one of the cornerstones in formulating its defense policy, including the decision to invade Ukraine